Given and acquired risk factors in cognitive decline, the development of Mild Cognitive Impairment, and Alzheimer’s Disease: results of a prospective, population-based, longitudinal study - Degen, Christina (2016)
In this dissertation, three articles on the relative roles of given and acquired risk factors in cognitive aging, the development of mild cognitive impairment and Alzheimer's disease are discussed. Data are derived from the Interdisciplinary Longitudinal Study of Adult Aging (ILSE). In the first article, the role of cholesterol Levels in midlife and during aging as well as the APOE genotype are considered. In the second article, the contribution of the COMT genotype on cognitive aging is investigated. In a third article, the role of Diabetes mellitus Type II on cognitive aging is discussed. I conclude that Lifestyle factors in midlife are more important than given risk factors (e.g. genes) for risk of pathological aging.
Keywords: Hochschulschrift